Strategy for the retention of human talent and job satisfaction, dispatch area in a poultry company in Trujillo: 2020 (SCIÉNDO INGENIUM, 2022)
The problem proposed in the presente investigation is: what is the strategy for the retention of human talent that a Trujillo poultry company must desing for the Dispatch area, which contributes to improving the level of job satisfaction: 2020?, it´s general objective was to design the strategy to retain the human talent in a poultry company in Trujillo for the despatch area, so that it contributes to improve the level of labor satisfaction supported on the strategy of total reward, as a model rewards management. For this purpose, it was made a diagnosis of the strategies and current actions to retain human talent as well as the job satisfaction of the area to determine its current situation. The unit of analysis of the study was the collaborator of the specified area, which was applied as a data collection instrument, a structured survey. It was used the non-experimental research design, of a transectional character and decriptive scope using the IBM SPSS Statistics tool. Finally, the proposal was presented with its respective objectives, actions and indicators for its subsequent implementation. The pillars of the proposal were: to offer recognition for the actions and goals achieved, to improve the work-life balance, to offter learning and development for personal growth and to reach a positive workplace.
Keywords: Human talent retention strategy; job satisfaction; total reward strategy